What Late-Career and Retired Women Engineers Tell Us: Gender Challenges in Historical Context. Issue 3 (2nd September 2019) - Ettinger, Laura; Conroy, Nicole; Barr, William
Abstract : Women engineers who graduated from college in the 1970s, a time in U.S. history when women's entry into engineering seemed most promising but failed to gain traction, offer important perspectives on the challenges facing women engineers in the past and today. To that end, we surveyed 251 women engineers from that generation to understand their perspectives and experiences. We found that the challenges faced by so many of the women engineers reflect gender issues that are deeply embedded in our interpersonal interactions and social structures – so much so that progress for women in engineering has been slow despite the anticipation that as more women went into the field, things would have gotten better. Although, as many participants noted, these challenges are rooted in gender inequity at social and institutional levels, participants often recommended individual-level solutions, encouraging young women to 'just do it' and persist in spite of the challenges. Our historical framing and gender analysis of participants' responses help to explain their beliefs about why change has been slow and why, despite the continued challenges, they have persisted and encourage young women to do the same.